Production of LM4 Feedstock for Thixoforming by using Cooling Slope Casting - Safian, M. A. H.; Salleh, M. S.; Hussein, N. I. S.; Sulaiman, M. A.; Yahaya, S. H. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
LM4 aluminium alloys are commonly used in automotive industry due to a combination of good fluidity and mechanical strength. In the present work, Cooling slope casting process was employed to produce A319 billets with near spherical morphology of primary Al-phase. To date, there are few studies that have investigated the association between the microstructural evolutions of alloy in a mould. The transformation of dendritic to non-dendritic microstructure is clearly obtained as the alloy filled the mould at the end of the cooling slope. The fundamental understanding issue of mechanism of the microstructural transformation through nucleation and fragmentation is enlightened. The alloy was poured from the inclined plate with length of 200mm, 300mm and 400mm at a pouring temperature of 660°C. The pouring was carried out on an inclined plate with tilt angle of 30°, 45° and 60°. Microstructures of specimens obtained using the optical microscope was examined to reveal the evolution of the microstructure. Grain size analysis of produced samples was carried out and the Vickers test was used to determine the hardness of the LM4 alloy. Experimental results showed that the flow length of the melt and tilt angle affected the microstructure of α-Al. Hence, it was determined that by pouring at 45° for 400mm length would increase the nucleation and led to more breaking of dendrite arms, thus improve the LM4 mechanical properties. In this study, the convection of melt at inclined cooling slope length played an important role on formation of non-dendritic primary of α-Al particle.